P069 Clinical Practice Guidelines Manuals and Toolkits. Are They Different Among Languages, Countries And Developers?. (15th August 2013) - Florez, I; Perez, Á; Prieto, L; Peña, E; Cañón, L
Abstract : Background: Manuals and Toolkits (MT) are standards for developing Clinical Practice Guidelines (CPG). Most developers have their own MT. There isn't enough information about characteristics of MT in other languages than English. Objective: To assess the characteristics of MT for developing CPG from different developers in English and Spanish. Methods: We searched electronic databases, national clearinghouses and non-electronic sources such as guidelines developer's sites. Epidemiologists independently assessed MT retrieved. Information about scoping, development group, Conflict of Interests (COI), updating, evidence systems among others, were extracted. Results: Twenty MT were retrieved, 8 in Spanish, and 12 in English. It is not clear how COI is declared and handled in most of the MT. GRADE and SIGN were the most recommended systems for assessment of quality of evidence, nevertheless many didn't recommend any system. Only 2 MT had a complete explanation about patient's participation. Three years is the most common recommendation for updating CPG. Only a few include an economic component. There isn't clarity in how recommendations are reported and how should be the external review of MT. Discussion: There is heterogeneity in CPG development. Spanish MT are less specific than English ones. It is important to improve quality of Spanish-language MT's, in order to enhance quality of Spanish CPG. There is an important lack of information about patient's participation and drafting of recommendations. Implications for Guideline Developers/Users: It's important to improve the contents and quality of MT in order to achieve high quality standards on CPG development for both developed and developing countries.